Designing benefit distribution driven innovation strategy for local enterprises under the global value chain system. (31st December 2021) - Wang, Ying; Mao, Xiangyu; Zameer, Hashim
Abstract : The threat from multinational enterprises to local enterprises in developing countries is increasing with the in‐depth development of global value chain cooperation. To increase the profit distribution of local enterprises in global value chain, it is necessary to analyze the cooperation strategy between local enterprises and multinational enterprises. In this paper, cooperative game theory is applied to form a better understanding of cooperation between local enterprises and multinational enterprises. The Shapley values under different cooperative models are analyzed. Based on the analysis, the paper provides some suggestions for local enterprises to enhance the profit distribution of cooperation with multinational enterprises.